2015
DOI: 10.1021/acs.biochem.5b00127
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Curvature Induction and Membrane Localization of the Influenza Virus M2 Protein Using Static and Off-Magic-Angle Spinning Solid-State Nuclear Magnetic Resonance of Oriented Bicelles

Abstract: A wide variety of membrane proteins induce membrane curvature for function, thus it is important to develop new methods to simultaneously determine membrane curvature and protein binding sites in membranes with multiple curvatures. We introduce solid-state NMR methods based on magnetically oriented bicelles and off-magic-angle spinning (OMAS) to measure membrane curvature and the binding site of proteins in mixed-curvature membranes. We demonstrate these methods on the influenza virus M2 protein, which not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…The size of the HA clusters was variable and spanned a large range of sizes, unlike the traditional definition of lipid rafts; this is likely driven by strong protein-lipid and protein-protein interactions and is consistent with data from previous reports (31,32). The M2 protein, whose cytoplasmic tail amphipathic helix has a major role in creating curvature of the membrane and in the scission of budding particles (26,(70)(71)(72)(73), is not raft associated but can bind cholesterol and yet does not cluster with raft markers (26,30,32,39,70). Many roles for the M1 protein in budding have been proposed, especially in binding to lipid bilayers, binding to the RNPs, and interacting with the cytoplasmic tails of HA, NA, and M2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The size of the HA clusters was variable and spanned a large range of sizes, unlike the traditional definition of lipid rafts; this is likely driven by strong protein-lipid and protein-protein interactions and is consistent with data from previous reports (31,32). The M2 protein, whose cytoplasmic tail amphipathic helix has a major role in creating curvature of the membrane and in the scission of budding particles (26,(70)(71)(72)(73), is not raft associated but can bind cholesterol and yet does not cluster with raft markers (26,30,32,39,70). Many roles for the M1 protein in budding have been proposed, especially in binding to lipid bilayers, binding to the RNPs, and interacting with the cytoplasmic tails of HA, NA, and M2.…”
Section: Discussionsupporting
confidence: 85%
“…However, the pattern of coclustering of HA and M2 may reflect the role that M2 is believed to play in scission; by occupying the periphery of HA patches, M2 is positioned to concentrate at the base of nascent budding virions (70). The amphipathic helix in the cytoplasmic tail of M2 has been shown to modify membrane curvature and is necessary for efficient membrane scission and virus release (28,(70)(71)(72). When the distribution of HA or NA is compared to that of a mutant M2 protein with cytoplasmic tail residues 71 to 73 replaced with alanine, a mutation known to impair virus growth, likely by interrupting the interaction of M2 with M1 (23), the magnitude of coclustering is dramatically reduced, suggesting a direct or indirect impact on HA or NA interactions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this C-terminal helix can be deleted entirely without greatly influencing the PT properties of the channel (42). This finding is also consistent with SSNMR structures of the channel (10,26,43), which show the amphipathic helix radiating away from the pore of the channel. For this reason our previous simulations (16,34) and many other computational and experimental studies (9,11,30,32,(44)(45)(46) have focused on the M2TM domain to investigate the AM2 proton conduction mechanism.…”
Section: Significancesupporting
confidence: 85%
“…M2 and Curvature Sorting/Induction. NMR techniques have shown that M2 can induce curvature in model membranes (45). In addition, M2 can stabilize and induce negative Gaussian curvature in membrane gyroid cubic phases (Ia3d) in a wide range of protein-lipid molar ratios (46).…”
Section: Discussionmentioning
confidence: 99%